The effects of a low carbohydrate diet on erectile function and serum testosterone levels in hypogonadal men with metabolic syndrome: a randomized clinical trial - Caio da Silva Schmitt; Carla Martins da Costa; José Carlos Stumpf Souto; Lorenzo Miron Chiogna; Zilda Elizabeth de Albuquerque Santos; Ernani Luis Rhoden; Brasil Silva Neto (BMC Endocrine Disorders, 2023)
Abstract Purpose Metabolic syndrome is a risk factor for several diseases. The relationship between metabolic syndrome and hypogonadism is well known. Our objetive is to assess whether a low carbohydrate diet can increase total serum testosterone and improve erectile function in hypogonadal men with metabolic syndrome. Methods An open label randomized clinical trial was conducted comparing a low carbohydrate diet and controls, during three months, in hypogonadal men with metabolic syndrome. Anthropometric measurements were evaluated as well as total serum testosterone levels, and symptoms of hypogonadism, using the ADAM and AMS scores, and sexual function using IIEF-5 score. Results Eighteen men were evaluated. Anthropometric measures were improved only in low carbohydrate diet group. The intervention group also had a statistically increase in IIEF-5 score and a significant reduction in AMS and ADAM scores (p < 0.001). The increase in serum total testosterone levels was statistically significant in the low carbohydrate group compared to the control group as well as calculated free testosterone (p < 0.001). Conclusions Low carbohydrate diet may increase serum levels of testosterone and improve erectile function in hypogonadal men with metabolic syndrome. However, larger studies are necessary to strongly prove the effectiveness of low carbohydrate diet in treating male hypogonadism.